Pine Emperor moths from KwaZulu-Natal use the same pheromone component previously isolated from Nudaurelia cytherea (Lepidoptera: Saturniidae) from the Western Cape - Scheepers, Luki-Marie; Allison, Jeremy D.; Slippers, Bernard; Rohwer, Egmont R.; Mc Millan, Patrick M.; Bello, Jan E.; Bouwer, Marc C. (African Entomology, 2023)
Nudaurelia spp. (Saturniidae) are sporadic pests of pine plantations in South Africa. Taxonomic uncertainty exists in South Africa with this group and represents an impediment to the development and implementation of pheromone-based management tactics. Populations from the Western Cape have been described as Nudaurelia cytherea while those from KwaZulu-Natal and Mpumalanga have been described as Nudaurelia clarki. We compared Cytochrome oxidase subunit I (COI) gene sequences from moths from the Western Cape, KwaZulu-Natal (KZN) and Mpumalanga regions. We also analysed female pheromone gland extracts with gas-chromatography electroantennographic detection (GC-EAD) and gas-chromatography-mass spectrometry (GC-MS) for moths from KwaZulu-Natal and Mpumalanga. COI gene barcoding sequences were identical for moths from the Western Cape, KwaZulu-Natal (KZN) and Mpumalanga regions providing preliminary evidence to suggest that these populations may be the same species. Based on the available literature, the morphology and origin of our samples suggests that pheromone analyses in this study were done on N. clarki. Male N. clarki antennae respond to two compounds in female extracts. One of these compounds was confirmed with a synthetic standard to be (Z)-dec-5-en-1-yl-3-methylbutanoate, the sex pheromone previously identified from N. cytherea. The identity of the second compound could not be confirmed. Both male and female antennae responded to four structurally related compounds in the synthetic pheromone standard. Field trials with custom-made traps confirmed attraction of N. clarki males to polydimethylsiloxane and polyisoprene lures loaded with synthetic (Z)-dec-5-en-1-yl-3-methylbutanoate.